"What do we want and how do we get there": A comparative content analysis of First Nations Comprehensive Community Plans in British Columbia. (31st December 2022) - Kobzik, Juraj; Krawchenko, Tamara
Abstract: First Nations are important regional development actors, and yet their development ambitions and goals have often been ignored or poorly understood by settler governments. Since 2004, the Canadian federal government has supported First Nations governments and Tribal Councils to develop Comprehensive Community Plans (CCPs)—community planning documents that are meant to set priorities and guide development in the medium to long term. This study employs a quantitative content analysis of all publicly available CCPs and related strategic planning documents in British Columbia in order to understand development priorities and in doing so, reveals a mismatch between the interests of First Nations and settler governments. Sommaire: Les Premières Nations jouent un rôle important dans le développement régional, et pourtant, leurs ambitions et objectifs de développement ont souvent été ignorés ou mal compris par les gouvernements colonisateurs. Depuis 2004, le gouvernement fédéral canadien a encouragé les gouvernements et les conseils tribaux des Premières Nations à élaborer des plans communautaires globaux (PCG) — des documents de planification communautaire qui sont censés établir des priorités et orienter le développement à moyen et à long terme. Cette étude utilise une analyse quantitative du contenu de tous les PCG et des documents de planification stratégique connexes publiquement accessibles en Colombie‐Britannique afin de comprendre les priorités de développement; ce faisant, l'étude révèle un décalage entre les intérêts des Premières Nations et ceux des gouvernements colonisateurs.